An integrated approach to the Quran: reflection on objectives of the Quran in Said Nursi’s views - Gilani, Sayyid Muhammad Yunus; Islam, Tazul (Pusat Tamhidi Universiti Sains Islam Malaysia, 2016)
This research presents BadÊÑuzzamÉn SaÑÊd NËrsÊ’s (1873-1960C.E.) views on MaqÉÎid al-Qur’Én. This scholar made MaqÉÎid al-Qur’Én the main subject matter of his grand work Risale-i Nur. Moreover, he presented an example of maqÉÎid based Qur’Énic exegesis in exclusive manner. This two dimensional feature of NËrsÊ’s work encourages a methodological study on his views of this subject. Thus, this Chapter explores the methodological aspect of his identification of MaqÉÎid al-Qur’Én. However, his brief biography and contribution to the Qur’Énic studies will be presented so that the impact of his intellectual makeup on his views of MaqÉÎid al-Qur’Én be understood